Insights into modulating the monastrol scaffold: Development of new pyrimidinones as Eg5 inhibitors with anticancer activity. Issue 10 (31st May 2022) - Thabit, Mohamed G.; Mostafa, Amany S.; Selim, Khalid B.; Elsayed, Magda A. A.; Nasr, Magda N. A.
Abstract: Based on modulation of the monastrol scaffold, two series of pyrimidinone derivatives, 3a–e and 5a–k, were designed, synthesized, and investigated for their in vitro anticancer activity. Compound 5j exhibited the most potent cytotoxic activity against four cancer cell lines, including HCT‐116, HeLa, HEPG‐2, and MCF‐7, with IC50 values of 3.75–5.13 µM, while proving to be safe in the normal human cell line WI‐38, with a selectivity index value of 13.7 on HCT‐116 cells. Compounds 3d, 3e, and 5h–j were further assessed for their Eg5 inhibitory activity, where 3d and 5h–j showed high Eg5 inhibition with IC50 values of 28.48, 24.22, 18.90, and 12.89 µM, respectively, when compared to monastrol (IC50 = 14.89 µM). Cell cycle distribution of HCT‐116 cells monitored with compound 5j illustrated that the cell cycle was arrested at the G2/M phase, with considerable apoptotic effect. A molecular docking study was performed to investigate the mode of action of the synthesized anticancer agents as Eg5 inhibitors. Abstract : Modulation of the monastrol scaffold gave two series of pyrimidinone derivatives as kinesin Eg5 inhibitors. Compounds 3d and 5h–j showed strong cytotoxic activity against different cancer cell lines with potent kinesin Eg5 inhibitory activity when compared to monastrol. Further investigations were performed, including cell cycle arrest and apoptosis studies.